Penggunaan Alat Peraga untuk Menigkatkan Literasi Sains Siswa pada Materi Bagian-Bagian Tumbuhan dalam Pembelajaran IPAS Kelas IV - Sofa Sofiana; Ade Maftuh; Rizki Hadiwijaya Zulkarnaen (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Science is a branch of science that is factual, either in the form of facts or events that are interconnected by cause and effect. Science was initially obtained through experiments (inductive) but over time, it was also developed with theory (deductive). Science in schools aims to ensure that students understand the processes and products of science, have a scientific attitude, and are able to become ethical citizens who are sensitive to environmental issues. The word "Alat Peraga" comes from two words, namely "alat" and "peraga". The main word in this term is "peraga", which functions to "demonstrate" or form a physical representation of a concept or understanding being explained. This physical form can be a real object, an imitation object such as a model, or a visual/audiovisual image. Science literacy (LS) comes from a combination of two Latin words, namely literatus, which means literate or educated, and scientia, which means knowledge. Scientific literacy is a person's ability to understand, communicate (both verbally and in writing), and apply scientific knowledge to solve problems, so that a person can develop a high attitude and sensitivity towards themselves and the environment in making decisions based on scientific considerations.